To solve for m∠1, we can use the fact that the sum of the measures of angles in a triangle is 180°.
Since ∠2 and ∠1 are adjacent angles in the triangle, we can write the following equation:
m∠1 + m∠2 + m∠3 = 180°
Given that m∠2 = 47°, we can substitute it into the equation:
m∠1 + 47° + m∠3 = 180°
Therefore, the equation to solve for m∠1 is:
m∠1 + m∠3 = 180° - 47°
Simplifying this equation gives us:
m∠1 + m∠3 = 133°
The m ∠ 2 = 47 ° . Use this information and the information on the diagram to answer all of the following parts. There are 6 parts worth 1 point each. a. Write an equation to solve for the m∠1.
1 answer